2021
DOI: 10.4103/jcar.jcar_14_21
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of lung carcinomas: A study on diagnostic, predictive, and prognostic markers using immunohistochemical analysis at a tertiary care center in Uttarakhand, India

Abstract: INTRODUCTION: Focused studies in different geographic regions would delineate the underlying biological differences and molecular alterations in non-small cell lung cancer (NSCLC) worldwide. Previous studies in literature have documented limited characterization by studying a minimal number of biological markers. This study was done to evaluate expression of multiple immunomarkers including diagnostic, prognostic, and predictive markers in NSCLC for its characterization. MATERIALS A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…In addition to the definition of mutation sites in the synchronous multiple primary samples, we also classified mutated genes with various diseases, BPs, and MFs through cluster analysis. Notably, mutations in ALK and PTEN are concordant in a range of tumor types, including lung adenocarcinoma, endometrial cancer, colorectal cancer, and triple‐negative breast cancer [ 15 , 16 , 17 , 18 , 19 ]. Previously, a study examining clinically relevant mutations in 91 different malignancies also found mutation sites in anaplastic lymphoma kinase (ALK) and PTEN [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the definition of mutation sites in the synchronous multiple primary samples, we also classified mutated genes with various diseases, BPs, and MFs through cluster analysis. Notably, mutations in ALK and PTEN are concordant in a range of tumor types, including lung adenocarcinoma, endometrial cancer, colorectal cancer, and triple‐negative breast cancer [ 15 , 16 , 17 , 18 , 19 ]. Previously, a study examining clinically relevant mutations in 91 different malignancies also found mutation sites in anaplastic lymphoma kinase (ALK) and PTEN [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…People often visit dentists when they are suffering from an illness [1,2]. Indonesia Health Data Profile 2010 revealed that pulp and periapical diseases are found in the 7 th of the ten most common diseases of outpatients in Indonesian Hospitals [3][4][5][6]. According to the Health Profile of Surakarta in 2014, the prevalence of pulp abnormalities and periapical tissue was 16,186 cases (2,56%) from the data of outpatient disease patterns in Surakarta Community Health Centre [4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Dental and oral disease is an essential issue of the health sector in general; however, in developing countries, there is a tendency to increase dental and oral diseases, one of which is dental caries, which, if untreated, can lead to tooth necrosis [1][2][3][4][5][6][7][8][9][10]. Treatment of tooth decay, such as caries or pulp necrosis, necessitates crown restoration and the creation of a post [11].…”
Section: Introductionmentioning
confidence: 99%